Molecular mass spectrometry imaging in biomedical and life science research - Pól, Jaroslav; Strohalm, Martin; Havlíček, Vladimír; Volný, Michael (Histochemistry and cell biology, 2010)
This review describes the current state of mass spectrometry imaging (MSI) in life sciences. A brief overview of mass spectrometry principles is presented followed by a thorough introduction to the MSI workflows, principles and areas of application. Three major desorption-ionization techniques used in MSI, namely, secondary ion mass spectrometry (SIMS), matrix-assisted laser desorption ionization (MALDI), and desorption electrospray ionization (DESI) are described, and biomedical and life science imaging applications of each ionization technique are reviewed. A separate section is devoted to data handling and current challenges and future perspectives are briefly discussed at the end.
Keywords: hmotnostní spektrometrie s elektrosprejovou ionizací; Animals; spektrometrie hmotnostní sekundárních iontů; Biomedical Research; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; lidé; Spectrometry, Mass, Secondary Ion; biomedicínský výzkum; biologické vědy; Spectrometry, Mass, Electrospray Ionization; Humans; zvířata; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Biological Science Disciplines